Awareness of maintenance needs for conserved heritage building among local authorities in Perak / Nurul Ain Nazira Mohd Asri and Amir Fasha Mohd Isa - Mohd Asri, Nurul Ain Nazira; Mohd Isa, Amir Fasha (2023)
Conserved heritage buildings play a vital role in preserving a region's cultural, historical, and architectural legacy. Their lifetime and continued significance depend on proper maintenance, which is crucial. The issues are the absence of comprehensive education and training programs focused on heritage building maintenance and Malaysia faces a shortage of skilled technical workers in the maintenance sector, contributing to subpar maintenance work. Thus, this study aims to determine how well local authorities in Perak are aware of the maintenance needs for historic buildings that have been conserved. In order to achieve the set objective of this study, quantitative data collection methods were adopted. The study conducted a survey questionnaire to local authorities in Perak to gather information about their awareness of maintenance needs, existing maintenance practice, challenges faced, and resources allocated for conserved heritage building. The results of this study can help the local authorities in Perak create more sensible strategies and regulations for the preservation and maintenance of conserved heritage buildings.